Expedition of F.A. Shcherbina to study the Kazakh steppe in the late ХІХ — early ХХ centuries - Amrina, M.S. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
Today, in the national historical science special attention is paid to the problem of source study. Over the years that had passed since Kazakhstan gained independence, a large number of valuable sources had been published and their scientific analysis had been carried out within the framework of various state programs. This article analyzes the source “The materials on the Kyrgyz (Kazakh) land use...”, collected by the expedition led by F.A. Shcherbina. This interesting source contains valuable information on the history of Kazakhstan in the late 19th and early 20th centuries.
ХІХ ғ. аяғы — ХХ ғ. басындағы қазақ даласын зерттеу бойынша Ф.А. Щербина экспедициясы
Экспедиция Ф.А. Щербины по изучению казахской степи в конце ХІХ–начале ХХ вв.
Keywords: Expedition; methodology; source; steppe region; F.A. Shcherbina; data processing; program; census; survey